Obstetric outcomes of monochorionic pregnancies conceived following assisted reproductive technology: A retrospective study - Mascarenhas, Mariano (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVES: The overwhelming numbers of twins following assisted reproductive technology (ART) are dichorionic twins, but monochorionic twins account for around 0.9% of post ART pregnancies. The data for post ART-monochorionic pregnancy outcomes are scarce due to the rarity of this condition. Hence, we evaluated the obstetric outcomes of monochorionic and dichorionic pregnancies conceived on ART. SETTINGS: University teaching hospital. STUDY DESIGN: A case–control study of monochorionic diamniotic (MCDA) and dichorionic diamniotic (DCDA) pregnancies conceived following ART treatment. Charts of all women who conceived following ART from 2008 to 2013 were screened. Among them, the monochorionic twins diagnosed in the first trimester were included and their obstetric outcome was followed-up. For comparison, an equal number of dichorionic twin pregnancies from age and body mass index matched mothers was selected. RESULTS: The baseline clinical characteristics were similar between the two groups. MCDA group had a higher miscarriage rate (50%) than the DCDA group (10%), with three seconds trimester miscarriages in the MCDA group. The live birth rates were lower in the MCDA versus DCDA group (40% vs. 90%). Among triplet pregnancies with a monochorionic component, the live birth rate was only 25%. CONCLUSIONS: Monochorionic pregnancies following ART have poorer obstetric outcomes when compared to dichorionic pregnancies. For monochorionic pregnancies following ART, intensive antenatal surveillance at a tertiary level obstetric and neonatal center may help optimize the outcome.